Endodontic management of a maxillary first premolar with 3 root canal. Case report using cone-beam computed tomography - Tapia Tapia, Gabriela (2022)
Endodontics is a branch of dentistry, which consists of treating the dental pulp, being important to make a correct diagnosis, collecting all the signs and symptoms. The upper first premolars present anatomical variations and there are probably failures during said therapy due to ignorance of it. According to several studies carried out through radiographs, diaphanizations and computed tomography, the upper first premolars can present three roots and three canals which vary from 0.5 to 6%, this anatomical variant being infrequent. To perform root canal treatment of a maxillary first premolar with 3 canals with the help of computed tomography. An 18-year-old male patient attends the FOUCE clinic for root canal treatment. When performing the intraoral exploration of the right maxillary first premolar, it showed coronal loss, negative thermal tests and positive to the vertical percussion test, in periapical radiography unusual anatomy is shown, computed tomography is performed locating 3 ducts: mesio-vestibular duct, disto-vestibular duct and palatine. Subsequently, the bio-chemo-mechanical preparation was carried out with manual protapper files, final irrigation protocol, thus ending with the obturation with the lateral technique. Thanks to the 3D image of the tomography, the mesio-vestibular, disto-vestibular, and palatal ducts will be detected, preventing a possible perforation due to the morphological complexity of this dental organ. Computed tomography is a test used for anatomical variations of dental organs, avoiding mistakes in the diagnosis and location of canals.